Effect Of Tool Wear On Turned Surface Using Continous Wavelet Transform - Thenesh, Selvam (Universiti Sains Malaysia, 2017)
This paper deals with the experimental study of the effect of tool wear on the surface machined profile uing continuous wavelet transform during turning operation of stainless steel workpiece using coated carbide tool inserts gred GC2025. By using a proper wavelet family to represent the profile of the turned surface, evaluation on which wavelet family is suitable to study the effect of tool wear on the turned surface’s profile is also done in this paper. Coefficients values such as mean, root-mean square and variance are extracted from the wavelet profile of the surface to observe the relationship of these coefficients values to the effect of the tool wear on the turned surface.